Digital Entrepreneurship di SMKN 6 Palembang Berbasis Website - Mirza Putri Andita; Azalia Mawarindani Indra; Muhammad Fajar Ariwibowo (Jurnal Pemberdayaan Umat, 2023)
Purpose: The aim of the community service program is to deliver knowledge, insight, and skills for teachers of SMK Negeri 6 Palembang on digital entrepreneurship using website Methodology/approach: The methodology employed in the community service program consists of delivering lectures, providing coaching, conducting monitoring, and facilitating discussions on the implementation of website Results/findings: The results of the program indicate an increase in participants' understanding of marketing concepts especially digital marketing. Furthermore, the participants are able to design theÂ  website using Canva to promote their product. Conclusion: The post-test conducted at the conclusion of the workshop confirms the success of the training, as participants demonstrated a solid grasp of the material and effectively applied the provided theories to create marketing content.